2016
DOI: 10.1177/2050312116642693
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of implantable cardioverter-defibrillator deactivation discussions: A qualitative study

Abstract: Background:There is a class I recommendation for implantable cardioverter-defibrillator deactivation discussions to occur between physicians and heart failure patients. Few studies have reported the patient’s perspective on the timing of implantable cardioverter-defibrillator deactivation discussions.Aim:To determine patient awareness, preferences and timing of implantable cardioverter-defibrillator deactivation discussions.Design:Grounded theory was used to collect and analyze interview data from 25 heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Although expert consensus statements and several guidelines recommend discussing deactivating the device shock function with patients who are nearing the end of their lives, and studies that have assessed patients' preferences have shown that most patients would prefer the shock function deactivation, 33,34 we found that nearly 75% of patients die with a fully active device. This reveals a gap both between guidelines and clinical practice and between patients' preferences and the reality of their last days of life.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Although expert consensus statements and several guidelines recommend discussing deactivating the device shock function with patients who are nearing the end of their lives, and studies that have assessed patients' preferences have shown that most patients would prefer the shock function deactivation, 33,34 we found that nearly 75% of patients die with a fully active device. This reveals a gap both between guidelines and clinical practice and between patients' preferences and the reality of their last days of life.…”
Section: Resultsmentioning
confidence: 74%
“…Our pool estimate is low, given the results of studies that have assessed patients' desire for reprogramming. 17,33,34 In one of these studies, the authors included patients who were not yet at the end of life and told them about the potential benefits and burdens of an active shock function. Then, the authors presented to them hypothetical common scenarios such as incurable disease and permanent inability to get out of bed; 71% of participants wanted the implantable cardioverter defibrillator reprogrammed in at least one of these scenarios.…”
Section: Main Findingsmentioning
confidence: 99%
“…[8][9][10][11] Although the predominant response from participants in our study was that they would raise the issue of device deactivation themselves, our findings also demonstrate that there are a number of teachable moments at which ICD recipients are open to receiving information about ICD deactivation and end-oflife issues. 9,11,31 Although clinicians may be uneasy raising the topic of ICD deactivation, 15,16 our study provides further evidence that the majority of patients support provider initiation of such discussions. 12 It has previously been noted that patients generally prefer to have discussions about ICD deactivation and end of life when their health status worsens, rather than during regular appointments.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, nine (45%) studies did not report the study design, 30 , 34 , 38 , 40 , 41 , 43 , 44 , 46 12 (60%) studies provided training to the study participants, 32 38 , 40 , 41 , 45 , 47 , 49 while four (20%) studies did not report information about patient training. 42 44 , 48 In addition, only five (25%) studies provided the method used to calculate the sample size 35 39 , 39 42 , 42 – 47 and only six (30%) studies investigated patient’s family members. 31 , 34 37 , 49 Finally, 17 (85%) studies provided information assessing patient knowledge and beliefs.30,32–35,37–45,47–49…”
Section: Resultsmentioning
confidence: 99%
“… 33 , 35 , 36 , 38 , 39 , 41 , 42 , 44 46 As for pretest and pilot testing, only four questionnaires (20%) mentioned that the survey had undergone cognitive pretesting or pilot testing. 33 , 35 , 39 , 44 Regarding validity, seven questionnaires (35%) assessed validity by asking patients if there were other aspects of care that were not mentioned in the questionnaires, 34 36 , 42 44 whereas only one questionnaire (5%) assessed internal consistency using Cronbach’s α with values of 0.74–0.87. 43 For acceptability, the time to complete the questionnaires ranged from 10 to 30 minutes, with nine studies (45%) reporting such data.…”
Section: Resultsmentioning
confidence: 99%